NEW SWITCHING SYSTEM IN SERVICE PT PLN PERSERO RAYA JAKARTA DISTRIBUTION AND BRANCH JATINEGARA TANGGERANG - Liga Bona Parta; Ir. Sapta Aji, SM, MM (Jurnal Sistem Informasi, 1998)
All the existing application system will depend on three major factors Hardware,software and brainware. To be able to help PT PLN is currently experiencingdifficulties in funding, the author tries to build a PC-based application system thattakes into account three main points earlier with good reason. Hardware that is used alot in the market and competitive price, besides cheap and easy maintenance.Software used is also very popular nowadays and the price is cheap realtif. Manybrainware that controls the hardware and software making it easier to develop.Application system which the authors make very suitable for Rayon and Ratingwhich will be built by PT PLN branch Jatinega ra.For can monitor potential consumers who meet the requirements to obtain electricitythen be made to the New Connection Service System that is integrated, so thatpotential customers will not wait too long to be able to obtain electricity.